Discrimination against Foreigners. The Wuerttemberg Patent Law in Administrative Practice - Sibylle H. Lehmann-Hasemeyer; Jochen Streb (Humboldt University Berlin, 2018)
Economists stress the leading role that inclusive institutions play among the various factors that foster a country's economic growth. In this article, we show that it might be misleading to mistake the codification of a formal rule for its effective administrative implementation. As the case of the German state Wuerttemberg demonstrates, a government's lip service to the principle of equal treatment does not guarantee that the local patent authority refrains from discriminating against foreign patentees by charging comparatively high patent fees. We conclude that the introduction of a stringent and formally fair patent law alone does not guarantee that foreign inventors' intellectual property rights are protected as well as those of the domestic patentees.
urn:nbn:de:kobv:11-110-18452/20239-3
Keywords: N13; N43; O34; 330